2013
DOI: 10.1029/2012jc008239
|View full text |Cite
|
Sign up to set email alerts
|

From the subtropics to the central equatorial Pacific Ocean: Neodymium isotopic composition and rare earth element concentration variations

Abstract: [1] Neodymium isotopic compositions (e Nd ) and rare earth element (REE) concentrations were measured for filtered surface to deep waters (112 samples) in the Southern Tropical Pacific. The relatively detailed picture of these tracer distributions allowed us to refine the areas where oceanic e Nd variations occur. e Nd values increase for most of the water masses flowing from Samoa to the Solomon Sea and in the Papua New Guinea (PNG) area, as already observed. Furthermore, water masses arriving from the easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
124
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(144 citation statements)
references
References 114 publications
19
124
0
1
Order By: Relevance
“…Budgetary estimates from diffuse benthic REE fluxes, such as SGD or from sedimentary pore water Greaves et al, 1999;Haley and Klinkhammer, 2003;Tachikawa et al, 2003;Johannesson and Burdige, 2007;Schacht et al, 2010;Johannesson et al, 2011Johannesson et al, , 2017Abbott et al, 2015a;Fröllje et al, 2016), suggest that they may dominate the flux of REEs to the oceans. Importantly, such diffuse, or at least hard to quantify, sources are consistent with deep-water isopycnal mixing of ε Nd signals off margins that cannot be explained through surface water sources (Grasse et al, 2012;Grenier et al, 2013). However, while a diffuse benthic source of Nd appears to better describe the dominant flux of REEs to the ocean, outstanding questions remain.…”
Section: Modern Ocean Rees and Nd Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Budgetary estimates from diffuse benthic REE fluxes, such as SGD or from sedimentary pore water Greaves et al, 1999;Haley and Klinkhammer, 2003;Tachikawa et al, 2003;Johannesson and Burdige, 2007;Schacht et al, 2010;Johannesson et al, 2011Johannesson et al, , 2017Abbott et al, 2015a;Fröllje et al, 2016), suggest that they may dominate the flux of REEs to the oceans. Importantly, such diffuse, or at least hard to quantify, sources are consistent with deep-water isopycnal mixing of ε Nd signals off margins that cannot be explained through surface water sources (Grasse et al, 2012;Grenier et al, 2013). However, while a diffuse benthic source of Nd appears to better describe the dominant flux of REEs to the ocean, outstanding questions remain.…”
Section: Modern Ocean Rees and Nd Isotopesmentioning
confidence: 99%
“…More recently, the emphasis of REE input to the oceans has shifted to greater consideration of a benthic continental margin source for REEs, as we will discuss further later (Spivack and Wasserburg, 1988;Jeandel et al, 1998;Goldstein and Hemming, 2003;Tachikawa et al, 2003;Arsouze et al, 2009;Rickli et al, 2009Rickli et al, , 2010Rickli et al, , 2014Carter et al, 2012;Grasse et al, 2012;Singh et al, 2012;Grenier et al, 2013;Wilson et al, 2013;Garcia-Solsona et al, 2014).…”
Section: Modern Ocean Rees and Nd Isotopesmentioning
confidence: 99%
“…Rempfer et al, 2011). A number of studies have recently contributed to filling these data gaps (see Lacan et al, 2012 for the global database before most of these new efforts; Grenier et al 2013;Haley et al, 2014;Osborne et al, 2014;Molina-Kescher et al, 2014), many of which were conducted within the framework of the international GEOTRACES program, (Singh et al, 2012;Stichel et al, 2012a, b;Chen et al, 2013b;Garcia-Solsona et al, 2014, Goswami et al, 2014. However, not all of these studies reported the complete set of REEs thus not exploring their full potential.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent observational studies promote Papua New Guinea as a typical area of boundary exchange of the high ε Nd sources to the Central Pacific Ocean (Amakawa et al, 2013;Grenier et al, 2013). This may be correct, but the involvement of diatoms cannot be ruled out, considering the higher ε Nd values near the surface and the depth of anomalous silica concentration.…”
Section: New Interpretation On Previous Model Studies and Observationsmentioning
confidence: 99%